THE PRAYER FOR PURITY IN MANUSCRIPTS OF THE IOSIFO-VOLOKOLAMSK MONASTERY (SHM, EPARCHIAL COLLECTION, NO. 160, 164 AND 165) - Cajka, Frantisek (Bohemica Olomucensia, 2020)
The study deals with three so far unexplored manuscripts of a prayer called Molitva o izbavljenii otъ blǫda (The Prayer for Purity). The text of the prayer is preserved in the manuscripts Jeparch 160, 164 and 165 from the fourth quarter of the 15th century to the twenties of the 16th century, which are part of the manuscript collection from the Iosifo-Volokolamsk Monastery (State Historical Museum, Eparchial Collection, Moscow). The close relationship of known manuscript versions of the prayer contained in the manuscripts of Czech Church Slavonic Forty Gospel Homilies by Pope Gregory the Great (Besedy na evangelije) and in the ancient Euchologium Sinaiticum strongly reinforces the hypothesis about the Great Moravian origin of their common archetype. The aim of the study is to reveal the relationship of the newly registered texts Jeparch 160, 164 and 165 to familiar texts. An integral part of the study also deals with an edition of the prayer and its critical apparatus based on the text of all known (edited) manuscripts of the prayer.
Keywords: Old Church Slavonic; Church Slavonic; paraliturgical texts; prayers